2021
DOI: 10.1093/cdn/nzab067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Milk Protein and Whey Permeate in Lipid-based Nutrient Supplements on the Growth and Development of Stunted Children in Uganda: A Randomized Trial Protocol (MAGNUS)

Abstract: Stunting is associated with cognitive impairment and later chronic disease. Previous trials to prevent stunting have had little effect, and no trials seem to have provided larger amounts of energy and high-quality proteins to already stunted children. We aimed to assess the effects of milk protein (MP) and whey permeate (WP) in large-quantity lipid-based nutrient supplements (LNS-LQ), among stunted children, on linear growth and child development. This was a randomized, double-blind, 2-by-2 factorial trial. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Of those children enrolled in the study, 600 were randomized to one of the 4 formulations, based on MP or soy protein and WP or maltodextrin using a 2 × 2 factorial design. As a reference, a further 150 children were randomized to no supplement, allowing us to assess the effect of LNS, irrespective of dairy [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those children enrolled in the study, 600 were randomized to one of the 4 formulations, based on MP or soy protein and WP or maltodextrin using a 2 × 2 factorial design. As a reference, a further 150 children were randomized to no supplement, allowing us to assess the effect of LNS, irrespective of dairy [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our secondary analysis, we also compared the intervention, i.e., LNS irrespective of ingredient (600 participants) against the unsupplemented reference group (150 participants). We carried out prespecified subgroup analyses for breastfeeding status, sex, stunting severity, and inflammation (defined as serum AGP, a slow reacting acute phase reactant, >1.2 g/l) to test for any further interactions [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was a cross‐sectional study using baseline data collected between February and September 2020 as part of the MAGNUS trial (Hannah Pesu et al, 2021 ) (ISRCTN13093195). As previously described (Hannah Pesu et al, 2021 ; Mbabazi et al, 2023 ), the study was conducted at two public health centres in Walukuba division and Buwenge town council in Jinja district of East Central Uganda (Busoga sub region). The current cross‐sectional study nested within the RCT uses the maximum available sample at baseline of 750 children.…”
Section: Methodsmentioning
confidence: 99%
“…This study reports secondary outcomes from the MAGNUS trial, a community-based randomized 2 × 2 factorial trial assessing the role of MP and WP in LNS on growth and development among stunted children (ISRCTN13093195). The primary outcome of the original trial was the effect of the intervention on height and knee-heel length as reported elsewhere [ 15 , 16 ]. The main outcome of the current study was child development.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously [ 15 ], children were individually randomized to one of the four supplements (1:1:1:1) or to no supplementation (4:1). The study was block randomized with variable block sizes of 10 and 20, and stratified by site.…”
Section: Methodsmentioning
confidence: 99%